Comorbidity before and after a diagnosis of inflammatory bowel disease. Issue 5 (22nd June 2021) - Bernstein, Charles N.; Nugent, Zoann; Shaffer, Seth; Singh, Harminder; Marrie, Ruth Ann
Summary: Background: Comorbidity is an important predictor of how disease course in inflammatory bowel (IBD) evolves. Aims: To determine pre‐diagnosis relative rates (RR) and post‐diagnosis hazard ratios (HR) of component diseases of the Charlson Comorbidity Index (CCI) in a cohort study of persons with IBD. Methods: The University of Manitoba IBD Epidemiology Database includes all Manitobans with IBD from 1 April 1984 through 31 March 2018 and matched controls. All outpatient physician claims and hospital discharge abstracts were searched for diagnostic codes for CCI component diseases. Some diseases were collapsed into one group such that we assessed 12 conditions. We report the RR of these conditions prior to IBD and the incidence of these diagnoses after IBD. Using Cox proportional hazards regression we report post‐diagnosis HR. Confidence intervals were adjusted for Bonferroni correction. Results: The RR of cardiovascular diseases, peripheral vascular diseases, chronic pulmonary diseases, connective tissue disease/rheumatic diseases, renal disease, liver diseases, peptic ulcer disease, and cancer were all increased prior to diagnoses of IBD compared to controls. All comorbidities were increased post IBD diagnosis. The increased HR for dementia in persons with Crohn's disease was a concerning novel finding. The increased association with paraplegia/hemiplegia was unexpected. For all comorbidities, except diabetes, the age at diagnosis was younger in IBD than controls. Conclusions: Persons with IBD have a higher comorbidity burden than persons without IBD. Optimal care plans for persons with IBD should include an assessment for other comorbidities that include just about every other organ system. Abstract : Hazard ratios of comorbid diseases diagnosed after IBD (Crohn's disease and ulcerative colitis) are diagnosed.